2016
DOI: 10.1182/blood-2016-05-714535
|View full text |Cite
|
Sign up to set email alerts
|

miR-146b antagomir–treated human Tregs acquire increased GVHD inhibitory potency

Abstract: Key Points tTregs express high miR-146b levels and downregulate TRAF6 mRNA and NF-κB activation, which is essential for tTreg function. miR-146b antagomir enhances in vitro and in vivo tTreg suppression and persistence as well as xenogenic GVHD lethality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…1A). Our previous study determined that miRNA-146b-5p increased TRAF6 expression in human tTregs (24). We further found that nTregs freshly isolated from human peripheral blood expressed TRAF6 mRNA to a greater degree than their non-Treg CD4+ counterparts ( Fig.Fig.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…1A). Our previous study determined that miRNA-146b-5p increased TRAF6 expression in human tTregs (24). We further found that nTregs freshly isolated from human peripheral blood expressed TRAF6 mRNA to a greater degree than their non-Treg CD4+ counterparts ( Fig.Fig.…”
Section: Resultsmentioning
confidence: 58%
“…We found that by antagonizing a specific microRNA (miR-146b), which targets TRAF6 transcript, they could enhance Foxp3 protein levels. Moreover, the in vitro and in vivo function of Tregs could be enhanced through a miR-146b antagomir (24). Interestingly, while increased Additionally, it now appreciated that Foxp3 function is largely facilitated by a number of coregulator molecules such as Eos, IRF-4, GATA-3, and other members of the Foxp3 "interactome" (4)(5)(6)40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the in vitro and in vivo function of Tregs could be bolstered through treatment with a miR-146b antagomir (Lu et al, 2016). Particularly, we found that by antagonizing a specific microRNA (miR-146b), which targets TRAF6 transcript, Foxp3 protein levels could be enhanced.…”
Section: Discussionmentioning
confidence: 86%
“…Particularly, we found that by antagonizing a specific microRNA (miR-146b), which targets TRAF6 transcript, Foxp3 protein levels could be enhanced. Moreover, the in vitro and in vivo function of Tregs could be bolstered through treatment with a miR-146b antagomir (Lu et al, 2016). It should be pointed out that this prior study attributed increased FOXP3 expression and Treg function to elevated NFjB activity, which can drive transcription of the Foxp3 gene (Chiffoleau et al, 2003;Long et al, 2009), but levels of Foxp3 mRNA were not specifically measured.…”
Section: Discussionmentioning
confidence: 92%
“…In an autoimmune setting, miR-146a expression can be induced by TNF-α (47), which in turn is stimulated by NF-κB, thus further confounding this complex regulatory network (Figure 4). Interestingly, another member of the miR-146 family, i.e., miR-146b, is highly expressed in CD4 + CD25 + FOXP3 + thymic-derived T regs and has been reported to promote survival, proliferation, and suppressor function of these cells by targeting TRAF6 and subsequently increasing NF-κB activity (54). …”
Section: Examples Of Snp–mrna–mirna Regulatory Network Controlling Omentioning
confidence: 99%